2017
DOI: 10.1186/s12915-017-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane dynamics and organelle biogenesis—lipid pipelines and vesicular carriers

Abstract: Discoveries spanning several decades have pointed to vital membrane lipid trafficking pathways involving both vesicular and non-vesicular carriers. But the relative contributions for distinct membrane delivery pathways in cell growth and organelle biogenesis continue to be a puzzle. This is because lipids flow from many sources and across many paths via transport vesicles, non-vesicular transfer proteins, and dynamic interactions between organelles at membrane contact sites. This forum presents our latest unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 180 publications
0
44
0
Order By: Relevance
“…In 2015, the Bao-Liang Song research group demonstrated that cholesterol transport is abnormal in ALD fibroblasts and in the Abcd1 mouse model for ALD as well as in other peroxisomal disorders. Low-density lipoprotein (LDL)-derived cholesterol was transported from the lysosome to the peroxisome in a manner that depended upon lysosomal synaptotagmin VII binding to the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate [PI(4,5)P 2 ] on the peroxisomal membrane (Chu et al, 2015;Hu et al, 2018;Islinger, Voelkl, Fahimi, & Schrader, 2018;Jin, Strunk, & Weisman, 2015;Luo, Jiang, Yang, & Song, 2018;Luo, Liao, Xiao, & Song, 2017;Stefan et al, 2017). While these findings were initially called into question by van Veldhoven et al in a letter to the editor (van Veldhoven, Baes, & Fransen, 2015), correctly identifying an error in Chu et al's method, a recent follow-up publication (Xiao et al, 2019) validates the initial Chu et al (2015) findings.…”
Section: Cholesterol Transport In Aldmentioning
confidence: 99%
“…In 2015, the Bao-Liang Song research group demonstrated that cholesterol transport is abnormal in ALD fibroblasts and in the Abcd1 mouse model for ALD as well as in other peroxisomal disorders. Low-density lipoprotein (LDL)-derived cholesterol was transported from the lysosome to the peroxisome in a manner that depended upon lysosomal synaptotagmin VII binding to the peroxisomal lipid phosphatidylinositol 4, 5-bisphosphate [PI(4,5)P 2 ] on the peroxisomal membrane (Chu et al, 2015;Hu et al, 2018;Islinger, Voelkl, Fahimi, & Schrader, 2018;Jin, Strunk, & Weisman, 2015;Luo, Jiang, Yang, & Song, 2018;Luo, Liao, Xiao, & Song, 2017;Stefan et al, 2017). While these findings were initially called into question by van Veldhoven et al in a letter to the editor (van Veldhoven, Baes, & Fransen, 2015), correctly identifying an error in Chu et al's method, a recent follow-up publication (Xiao et al, 2019) validates the initial Chu et al (2015) findings.…”
Section: Cholesterol Transport In Aldmentioning
confidence: 99%
“…Cellular cholesterol homeostasis depends critically on sterol flux through LE/LYSs, but the pathways and molecular mechanisms of sterol trafficking between these organelles and other membranes are poorly defined 51,52 . In Niemann-Pick type C2 disease, cholesterol and other lipids build up due to lack of a small sterol-transfer protein, NPC2, in the lumen of LE/LYSs.…”
Section: Discussionmentioning
confidence: 99%
“…The best characterized machinery of this type is the lipid transfer by Osh4 transporting sterols from the ER to the trans ‐Golgi . Not only sterols, but also glycerophospholipids are actively transported by non‐vesicular traffic . Here, the counterflow and turnover of PI4P serves a dual role in energizing lipid transport and marking organelle identity.…”
Section: Compendium Of Physicochemical Membrane Propertiesmentioning
confidence: 99%